Managing Universities for the Entrepreneurial Society: Entrepreneurial Loops and Innovative Teaching Initiatives - Ewango-Chatelet, Aurelie (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2019)
Drawing upon the entrepreneurial spirals concept, this article examines how managerial practices influence entrepreneurial intent in traditional academic activities. The international inquiry analyses innovative teaching into six business schools in France, Canada and Morocco. At the complex interplay between individual goals and organizational objectives, three entrepreneurial loops are identified: converging, diverging and absence of loop. Findings suggest that university management remains a challenge as an appropriate balanced management is required for the changing university’s mission towards social and economic well-being. The conditions of successful academic entrepreneurial activities are outlined across three propositions.